2002
DOI: 10.1097/00005537-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 Expression in Human Thyroid Carcinoma and Hashimoto's Thyroiditis

Abstract: We have shown that cyclooxygenase-2 is expressed in thyroid carcinoma and thyroid epithelium from patients with Hashimoto's thyroiditis but not in normal thyroid. The expression of COX-2 in both of these thyroid pathologies may provide a basis for the relationship between carcinogenesis and autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 26 publications
6
55
0
4
Order By: Relevance
“…The cells residing within thyroid follicles of large thyroid tumors expressed the myeloid markers CD11b and F4/80, a phenotype consistent with macrophages (34), a cell type known to secrete a variety of mediators contributing to the cytokine expression profile observed in RP3-transgenic thyroids (35). Indeed, intrafollicular macrophages, fibroblasts, and vascular endothelium produced Il6, whereas only Cox2 protein was found within thyroid epithelial cells, data consistent with the expression of RET/PTC proteins in PTC (29). Thus, the transformed thyroid microenvironment may be modeled as a complex mixture of resident thyroid epithelial cells producing chemokines that induce the infiltration of inflammatory cells, including activated macrophages, that respond to these mediators and secrete additional factors.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The cells residing within thyroid follicles of large thyroid tumors expressed the myeloid markers CD11b and F4/80, a phenotype consistent with macrophages (34), a cell type known to secrete a variety of mediators contributing to the cytokine expression profile observed in RP3-transgenic thyroids (35). Indeed, intrafollicular macrophages, fibroblasts, and vascular endothelium produced Il6, whereas only Cox2 protein was found within thyroid epithelial cells, data consistent with the expression of RET/PTC proteins in PTC (29). Thus, the transformed thyroid microenvironment may be modeled as a complex mixture of resident thyroid epithelial cells producing chemokines that induce the infiltration of inflammatory cells, including activated macrophages, that respond to these mediators and secrete additional factors.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, to evaluate the coincident expression of RP3 with a marker of inflammation, the protein Cox2 was used since it is an intracellular enzyme induced during thyroid inflammatory responses and can be localized to individual cells using immunohistochemical staining (29). Data in Fig.…”
Section: Coordinate Expression Of Inflammatory Mediators and Rp3 In Dmentioning
confidence: 99%
“…[26][27][28][29] Thyroid tumors generally express higher levels of COX-2 than normal tissues and thyroid tissues from patients with thyroiditis. [26][27][28][29] Thromboxane A2 (TXA 2 ) synthase and prostaglandin (PG) I 2 synthase are enzymes located downstream from COX-1 and COX-2, and catalyze synthesis of PG H, TXA 2 and PGI 2 ( Figure 1). TXA 2 stimulates platelet aggregation, while PGI 2 inhibits aggregation of platelets.…”
mentioning
confidence: 99%
“…But Hashimoto's thyroiditis might represent the host immune response to preexisting PTC; PTC might be induced or triggered by preexisting Hashimoto's thyroiditis, and a common mechanism, such as imbalance between apoptotic/antiapoptotic pathways, may be involved in the two diseases [26]. Previous studies have reported that chronic inflammation responses such as those associated with autoimmune thyroiditis might act as carcinogens [27] or rearranged in transformation/PTC oncogene that is known to be highly specific to PTC might be expressed in Hashimoto's thyroiditis [28]. Chronic inflammatory change may occur in the whole thyroid gland with multifocal foci, so increase the incidence of multifocality and contralateral cancer.…”
Section: Discussionmentioning
confidence: 99%